Stability of vaccine strains of seasonal live attenuated influenza vaccines when adapted to MDCK cell culture - Victoria A. Matyushenko; Arina D. Kostromitina; Ekaterina A. Stepanova; Larisa G. Rudenko; Irina N. Isakova-Sivak (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Currently, the vast majority of influenza vaccines in the world are produced using developing chicken embryos as substrate, but there is an urgent necessity for transferring vaccine production to continuous cell lines, which would ensure uninterrupted production during an avian influenza pandemic and also allow the vaccine to be administered to individuals with chicken protein allergies. When vaccine strains of live attenuated influenza vaccine (LAIV) grow in mammalian cells, adaptation mutations can occur that may affect the antigenic and immunogenic properties of the vaccine.